The Influence of Gender-Sensitive Pregnant Women's Class on Maternal Self-Reliance Readiness in the Face of Childbirth and Complication Prevention - Yudhia Fratidhina; Novita Rina Antarsih; Sri Mulyati; Fidya Aminin; Nina Herlina (Universitas Aisyah Pringsewu, 2021)
High Maternal Mortality Rate from sustainable development goals and evaluation of KIH (Pregnant Women Class) as one of the government programs to lower AKI is still likely to be implemented. This study aims to develop KIH with gender-sensitive participatory models especially in the independence of mothers facing childbirth. A method used with a cross-sectional study design, which is analyzed using quasi-experiments with control group design. In Jakarta, most of its respondents do not work while in Pangkal Pinang most of the respondents’ work. There is a significant difference of Access with a greater average value difference for the Pangkal Pinang area of 12.06; Participation with a greater average value difference for Pangkal Pinang of 5.00; control with a greater average value difference for the Pangkal Pinang area of 9.00; Benefits with a greater average value difference for the Pangkal Pinang region of 8.00; There is no meaningful difference in self-reliance in the face of childbirth and complications (access, participation, control, and benefits) between the intervention and control groups after the intervention of the gender-sensitive participation model of Jakarta and Pangkal Pinang areas. There are meaningful differences in knowledge and attitudes, access, participation, control, benefits, and independence of access in the face of childbirth in the intervention group before and after the intervention of gender-sensitive participatory models in the Jakarta and Tanjung Pinang areas.Abstrak: Tingginya Angka Kematian Ibu (AKI) dari target Sustainable Development Goals (SDG’s) dan evaluasi KIH (Kelas Ibu Hamil) sebagai salah satu program pemerintah untuk menurunkan AKI masih berpeluang untuk dilaksanakan. Penelitian ini bertujuan untuk mengembangkan KIH dengan model partisipatif sensitif gender terutama dalam kemandirian ibu menghadapi persalinan. Metode yang digunakan dengan desain studi potong lintang (cross sectional), yang dianalisis menggunakan dengan quasi eksperiment with control group design. Karakteristik responden usia minimal 30 tahun dan usia maksimal 39 tahun, mayoritas multipara, dan mayoritas pendidikan tinggi. Jakarta sebagian besar respondennya tidak bekerja sedangkan Pangkal Pinang sebagian besar respondennya bekerja. ada perbedaan bermakna Akses dengan selisih nilai rata-rata lebih besar untuk wilayah Pangkal Pinang sebesar 12,06 dibandingkan wilayah Jakarta sebesar 5,53; Partisipasi dengan selisih nilai rata-rata lebih besar untuk Pangkal Pinang sebesar 5,00 dibandingkan wilayah Jakarta sebesar 3,90; kontrol dengan selisih nilai rata-rata lebih besar untuk wilayah Pangkal Pinang sebesar 9,00 dibandingkan wilayah Jakarta sebesar 6,60; Manfaat dengan selisih nilai rata-rata lebih besar untuk wilayah Pangkal Pinang sebesar 8,00 dibandingkan wilayah Jakarta sebesar 6,067; Tidak ada perbedaan bermakna kemandirian dalam menghadapi persalinan dan komplikasi (akses, partisipasi, kontrol dan manfaat) antara kelompok intervensi dan kontrol setelah dilakukan intervensi model partisipasi sensitif gender wilayah Jakarta dan Pangkal Pinang. Adanya perbedaan bermakna pengetahuan dan sikap, akses, partisipasi, kontrol, manfaat, dan kemandirian akses dalam menghadapi persalinan pada kelompok intervensi sebelum dan sesudah intervensi model partisipatif sensitif gender baik di wilayah Jakarta maupun Tanjung Pinang.